Upper gastrointestinal endoscopy performed by nurses: scope for the future?. Issue 8 (15th July 2003) - Smale, S; Bjarnason, I; Forgacs, I; Prasad, P; Mukhood, M; Wong, M; Ng, A; Mulcahy, H E
Abstract : Background: Previous researchers have shown that non-medical endoscopists can perform lower gastrointestinal endoscopy as safely and effectively as medical staff. However, it is not known if upper gastrointestinal endoscopy performed by medical and non-medical endoscopists in clinical practice yields similar results in terms of performance, patient discomfort, and satisfaction. Aim: To determine differences in the yield of diagnosis for significant disease during upper gastrointestinal endoscopy performed by nurse and medical endoscopists and to measure patient discomfort, satisfaction, and attitudes towards future endoscopy. Patients: This two part study included 3009 patients in a retrospective analysis and 480 in a prospective study. Methods: The first part of the study assessed indications for endoscopy, diagnoses, and procedures performed by medical and nurse endoscopists. In a second prospective study, 480 patients were included to determine the association between endoscopist type and sedation, patient anxiety, discomfort, satisfaction, and attitudes towards future sedation. Results: No patient refused endoscopy by either a nurse or medical endoscopist and there were no complications in either group. Nurses performed 1487 procedures and reported fewer endoscopies as "normal" than medical staff (p=0.006). Multivariate analysis showed that male sex, older age, inpatient status, dysphagia, and gastrointestinal bleeding, but not endoscopist type, were all associated with significant disease. In relation to discomfort and satisfaction, a similar proportion of patients received sedation in both groups (p=0.81). There were no differences in pre-procedure anxiety (p=0.61), discomfort during intubation (p=0.97), discomfort during examination (p=0.90), or post-procedure examination rating (p=0.79) in patients examined by medical or nurse endoscopists. Conclusion: Experienced nurses perform routine diagnostic gastroscopy safely in everyday clinical practice and with as little discomfort and as much patient satisfaction as medical staff.